’al’Baḥrain ’abr ’al-ta’rīḫ. ’al-ǧuz’ ’al-’awwal/Bahrain through the Ages. Vol. 1. Bahrain 1402 A. H. = 1982 A.D. Third Edition - Al Khalifa, Shaikh Abdullah bin Khalid
Al-Šaiḫ ’Abdullāh ’ibn Ḫālid ’Āl Ḫalīfah, ’Abdu’l -Malik Yūsuf ‘al-Ḥamar; First Edition: 1389/1969. Second Edition: 1391/1971; in Arabic. The first two chapters contain material and illustrations which are relevant to KeiBi].